Ghosts, Vampires, and Werewolves: Eerie Tales from Transylvania - Spariosu, Mihai; Benedek, Dezso; Kubinyi, Laszlo, 1937- (New York : Orchard Books, 1994)
Includes sixteen tales from Transylvanian folklore, arranged in three sections: Ghosts, Vampires, and Werewolves; Haunted Treasures; and Eerie Fairy Tales.
Includes bibliographical references.
Keywords: Ghosts -- Romania; Vampires -- Romania; Warewolves -- Folklore; Supernatural